Performance Analysis of Nanofluid-based Photovoltaic Thermal Collector with Different Convection Cooling Flow - Zainal Arifin; Nuha Khairunisa; Budi Kristiawan; Singgih Dwi Prasetyo; Watuhumalang Bhre Bangun (Civil Engineering Journal, 2023)
Using solar energy through photovoltaic (PV) panels has excellent potential as an alternative energy source. However, the problem of high operating temperatures causing a reduction in work efficiency needs to be addressed. This study aimed to analyze the development of a cooling system to increase PV panels' electrical and thermal efficiency. The research involved analyzing the use of TiO2, Al2O3, and ZnO working fluids by adding 0.5 vol% to water in an active cooling method. The cooling system involved a rectangular spiral and a rectangular tube behind the PV panel. A solar simulator simulated solar radiation with intensity variations to analyze the cooling system's performance in different working conditions. The results showed that the heat exchanger with a nanofluid configuration reduced the panel temperature by 14 oC, which increased the electrical efficiency by up to 4.7% in the ZnO nanofluid. In the rectangular spiral configuration, the ZnO nanofluid reduced the panel temperature from 60 to 45 oC, increasing the Isc value from 2.16A to 2.9A and the Voc value from 21.5V to 23V. This resulted in a maximum power increase of the panel to 53W.Â Doi: 10.28991/CEJ-2023-09-08-08 Full Text: PDF